International market assessment: Site selection in service firms - Ute Reuter; Wolfgang Burr (Universität Stuttgart, Betriebswirtschaftliches Institut, Abteilung I - Forschungs-, Entwicklungs- und Innovationsmanagement, 2011)
Location is a neglected factor within international scientific research in spite of its increasing importance in corporate practice. Selection of severely flawed or completely unsuitable sites can lead to partly or complete withdrawal from country markets, closure of subsidiaries and financial losses. Quality and efficiency of site selection are very important for internationalization success, but still surprisingly undistinguished in recent literature. Within this paper, requirements for site evaluation and selection are derived. A systematic site selection methodology capable of increasing effectiveness, decision quality and efficiency in service firms is developed. Porter's national diamond approach is combined with resource-based theory of the firm and dynamic capabilities reasoning to explain the usage of site selection criteria. Transaction costs theory and agency theoretical reasoning are used to account for specific requirements of site selection. Thus, a stepwise site selection methodology is derived from theory and is implemented, further developed and evaluated in two actions research-based case studies. Using publicly available data, explicit definition, weighting of indicators, systematic data mining and evaluation considerably increases decision transparency in site selection and reduces time expenditure. In both case studies, effectiveness and efficiency increased due to utilizing the proposed site selection methodology.
urn:nbn:de:101:1-201203074530
Keywords: 650; Foreign Direct Investment; Globalisation; International management; Internationalization; Market research; Professional service firms